Dreaming of a duke like you - Bennett, Sara, 1957- (Romancing the Dukes, 2023)
"Raised in a foundling home and now proprietor of a successful club, Gabriel Cadieux hasn't ever been welcomed by polite society. But when he discovers he's the legitimate heir to a dukedom, he must make a choice: accept the debt-ridden title and the trappings of the peerage who shunned him or decline and leave his six rebellious half sisters to fend for themselves. As much as he hates the idea, Gabriel can't abandon his siblings, even if it means making a deal with the most frustrating--and aggravatingly beautiful--woman he's ever met. Vivienne Tremeer storms into Cadieux's club with one thing on her mind: get the loathsome owner to discharge her brother's gambling debts. So when Gabriel offers her a trade--if she'll teach his wild sisters the ways of the ton, he'll clear the notes--she has no choice but to accept. But with her reputation already on a knife's edge, falling for the duke could cause the scandal of the season"--